Morphometric measurements of Africanized honeybee queens kept in an incubator or in queen banking (Acta Scientiarum. Animal Sciences, 2015)
This study aimed to estimate live weight, the length and the width of wing and abdomen and the length, the width and the height of thorax in newly emerged Africanized honeybee queens up to 192 hours and their influence on final quality regarding appropriate storage techniques in queen banking or incubator and to verify the possibility of using these parameters as selection criteria in honeybee breeding programs. Queen honeybees were produced in summer, autumn and winter. The queen production method used throughout the experiments was adapted from Doolittle, and 68 the queens were weighed at emergence. Data were analyzed in R software by regression analysis of queen weight at emergence according to life time after emergence, in two types of storage. The weight of queens emerged in queen banking and incubator was significantly different (p < 0.05), with mean values of 165.61 and 157.04 mg, respectively. Queens kept in an incubator and in queen banking showed no significant differences (p > 0.05) in wing length, abdomen length and thorax height. The weight of queen at emergence can be used as a selection criterion in honeybee breeding programs.